Attitude of Agriculture Collegian towards Opting Farming as a Profession (Indian Journal of Extension Education, 2018)
Most agriculture graduates are absorbed in public and private sector jobs and only few are observed to have actually taken up farming as a life work which is in agreement to the general belief that farming is a non-professional, less prestigious and less profitable career to be taken up by the students after their graduation. Thus this exploratory study was carried out purposively on the B.Sc. (Agriculture) fourth year students in College of Agriculture, Imphal which is one of the allied colleges of Central Agricultural University, Imphal to study the attitude of agriculture collegian towards opting farming as a profession through personal interview of the respondents. From the study it is found that 90.62 per cent of the respondents had favourable attitude towards opting farming as a profession. From the study it is concluded that efforts are required to convert the covert attitude into overt behaviour such that graduates adopt farming as their profession so as to harness the potential of graduates and agriculture at the same time.